Time trends in cerebral palsy incidence in correlation with development of perinatal and neonatal care in Maribor (1988–2003): Smeri gibanja pojavnosti cerebralne paralize v odvisnosti od razvoja perinatalne medicine in intenzivnega zdravljenja novorojenčkov v Mariboru (1988–2003) - Seme-Ciglenečki, Polona; Burja, Silva; Hajdinjak, Dušanka; Mičetić Turk, Dušanka (Acta Medico-Biotechnica, 2021)
Purpose: To investigate time trends in cerebral palsy (CP) incidence in correlation with development of perinatal and neonatal intensive care in Maribor, Slovenia.Methods: A population–based study covering the 52.450 live births (1988– 2003) at the Department of Perinatology, University Clinical Center, Maribor and residents in one of the five communities of the Maribor region on January 1, 2006. Multiple sources were used. Neuropediatrician and other professional medical records were evaluated for all children at the rehabilitation units. The prevalence of CP was analyzed in yearly cohorts according to birth weight, gestational age, type of CP, and degree of disability.Results: Calculated crude mean prevalence of CP for this population group was 3.7/1000 infant survivors, 2.7/1000 for preterm CP, and 1/1000 for term CP, and 44% were Gross Motor Function Classification System levels I and II. Spastic diplegia was the most prevalent subtype of CP. The increase in CP rates in 1999, 2000 and 2001 could be explained by improved survival of preterm infants at 28–32 weeks gestation. The neonatal mortality rate has declined in Maribor significantly from 6.6/1000 live births in 1997 to 3.1/1000 in 2001 and 1.8/1000 in 2009.Conclusion: Progressive changes in perinatal and neonatal intensive care in Maribor since 1994 have led to a fall in the early neonatal mortality rate, and this increase in survival of preterm infants has increased CP morbidity rate.
Keywords: cerebral palsy; perinatal care; neonatal mortality; neo-natal care